Enhancing Plasticity and Compaction Properties of Clay Soil- Subgrade Using Iron Ore Tailings: A Case Study of Kabale District. - Mukago, Andrew (Kabale University, 2024)
The workability of any soil, when used as a construction material, is greatly affected by its plasticity and compaction characteristics. Investigating the Effect of Iron Ore Tailings on the Plasticity and Compaction Properties of Clay Soils" aimed to explore the potential impact of iron ore tailings on the engineering properties of clay soils. Clay soils are widely used in construction and civil engineering projects, but their plasticity and compaction properties can vary significantly depending on their composition and environmental factors. This project sought to evaluate how iron ore tailings interact with clay soil samples and influence the soil's mechanical behavior by introducing them. Iron ore tailings are waste generated during the mineral processing process and are the main component of industrial solid waste. If not properly treated, Iron ore tailings cause many hazards such as land occupation, environmental pollution, and safety hazards among others. Despite the abundance of clay soils in construction projects, their plasticity and compaction properties can be detrimental to structural integrity. The main objective of this research was to enhance the plasticity and compaction properties of clay soil subgrade using iron ore tailings and the specific objectives were to determine the physical and mechanical properties of Iron Ore Tailings and Clay, study the change in the; plasticity of clay soils at different percentages of Iron Ore Tailing’s Content (10%, 20% and 30%), compaction property of clay soils at different percentages of Iron Ore Tailing’s Content and to determine the minimum percentage that gives a positive change in the enhancement of plasticity and compaction properties of clay. Tests like particle size distribution analysis, natural moisture content, and Atterberg limits were carried out to classify, determine the amount of water naturally present in samples, and determine the plasticity index of the soil and iron ore tailings, respectively. Tests like specific gravity and water absorption, MDD, and CBR were carried out on clay soil and the IOT samples to extensively know their physical compaction characteristics. From the CBR test for clay (which served as the control experiment); the moisture content of 12.7% before compacting was obtained. The swell values of the sample of 0.13%, 0.09%, and Enhancing Plasticity and Compaction Properties of Clay Soil- Subgrade Using Iron Ore Tailings. (case study: Kabale district) 0.03% for light compaction, medium compaction, and heavy compaction respectively were obtained. The CBR values obtained at 2.5mm penetration were 3.5%, 4.4%, and 7.8% for light, medium, and heavy compaction respectively; at 5.0mm penetration were 3.3%, 4.1%, and 6.9% for light, medium, and heavy compaction respectively. CBR values of 3.7%, 5.0%, and 5.9% for 90%MDD, 93%MDD, and 95%MDD respectively were obtained.